Citra Destinasi Air Terjun Madakaripura: Analisis Sentimen Wisatawan di Google Review - Florenza, Lovinda Lusya; Nugraha, Awaludin; Withaningsih, Susanti; Dienaputra, Reiza D.; Hermanto, Bambang; Oktavia, Dina (JURNAL SOSIAL HUMANIORA (JSH), 2025)
This study examines the digital destination image of Madakaripura Waterfall by analyzing tourist sentiments expressed in Google Review posts from January 2024 to November 2025. The research is motivated by unique governance issues, particularly the period of temporary closure declared by the local government while on-site operations continued, which triggered diverse tourist responses on digital platforms. The analysis was conducted using the Naïve Bayes sentiment classification algorithm, word cloud visualization, word frequency analysis, and thematic analysis. The findings reveal that positive sentiment dominates (69.44%), primarily driven by appreciation for the natural beauty, scenic landscape, and the unique “eternal rain” phenomenon. Neutral sentiment (8.18%) mainly consists of factual descriptions related to environmental conditions, accessibility, and practical visitor information. Meanwhile, negative sentiment (22.38%) is largely influenced by governance-related issues, including the forced use of local guides, unclear pricing systems, and uncomfortable interactions with local stakeholders. These governance and service-quality issues are identified as the main threats to the destination’s digital image. The study proposes several strategic recommendations, including strengthening community-based tourism (CBT), implementing transparent and standardized pricing, enhancing capacity building for local guides, and optimizing social media–based visitor feedback mechanisms.